At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
m=9
c=-4
Step-by-step explanation:
If you use the formula y=mx+c and compare it to y=9x-4, you can see that m=9 and c=-4
Answer:
- m = 9
- b = -4
Step-by-step explanation:
- Our equation
=> y = mx + b
- Given equation
=> y = 9x - 4
Now, let's compare both the equations.
=> y = mx + b = y = 9x - 4
We can clearly see that 'm = 9 and b = -4'
Therefore:
- m = 9
- b = -4
Hoped this helped.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.